Revolution of blood cancer treatment in the oral cavity: Breakthroughs in nanotherapy - Pavithra Bharathy; Elizabeth Rani E; Punniyakoti V. Thanikachalam (Oral Oncology Reports)
This comprehensive review explores the potential of nanotherapy in the treatment of blood cancers, specifically leukemia, lymphoma, and myeloma, in the oral cavity. Nanoparticles (NPs) made from organic and inorganic materials have shown promise in delivering therapeutic substances to cancer cells, enhancing their pharmacological efficacy, and reducing their systemic toxicity. Different types of nanoparticles, such as liposomes, extracellular vehicles, and polymeric nanoparticles, have been studied for their effectiveness in targeting cancer cells. Nanotherapy has also been investigated for overcoming drug resistance, targeting cancer stem cells, bypassing efflux pumps, and gene silencing. Clinical trials and research findings have demonstrated the potential of nanotherapy for improving outcomes in patients with acute myeloid leukemia, chronic lymphocytic leukemia, Hodgkin lymphoma, non-Hodgkin lymphoma, and multiple myeloma. However, challenges exist in addressing the heterogeneity of blood cancers in the oral cavity, navigating the tumor microenvironment, overcoming drug resistance, and modulating immune evasion. Future directions include individualized treatment plans, multifunctional nanoparticles, combination therapies, and improved nanoparticle design. The translation of these breakthroughs into clinical practice requires collaboration among researchers, physicians, and industry stakeholders. Overall, nanotherapy holds promise for more effective and less invasive treatments for blood cancer in the oral cavity.